2016
DOI: 10.1016/j.jare.2015.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Selective determination of dimenhydrinate in presence of six of its related substances and potential impurities using a direct GC/MS method

Abstract: A novel simple, direct and selective gas chromatography–mass spectrometry (GC/MS) procedure was developed for the determination of the antihistamine drug dimenhydrinate (DMH) in presence of six of its related substances and potential impurities, namely, diphenylmethane, diphenylmethanol, benzophenone, orphenadrine, caffeine and 8-chlorocaffeine. The method involved resolution of the underivatized compounds using a trifluoropropylmethyl polysiloxane (Rtx-200) capillary column and the mass spectrometric detectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…The DMH calibration curve was linear with a measurement coef icient (R2) of between 50-500 µg / mL= 0.9982. For the DMH test in tablets with recoveries > 96.80%, the proposed approach has been used successfully (Belal et al, 2016).…”
Section: Pro Iling Of Impurities By Gc/msmentioning
confidence: 99%
“…The DMH calibration curve was linear with a measurement coef icient (R2) of between 50-500 µg / mL= 0.9982. For the DMH test in tablets with recoveries > 96.80%, the proposed approach has been used successfully (Belal et al, 2016).…”
Section: Pro Iling Of Impurities By Gc/msmentioning
confidence: 99%
“…On the other hand, the DMH and CIN combination is not officially included in any pharmacopeia. The literature review revealed a spectrophotometric, 14 electrochemical 15 and chromatographic [16][17][18] methods for determination of DMH and its impurities. CIN was assayed spectrophotometrically, 19,20 electrochemically 21,22 and by chromatographic methods [23][24][25][26][27][28] either alone or in combination with other drugs and/or impurities.…”
Section: Introductionmentioning
confidence: 99%
“…A literature survey revealed that DMH was analyzed by spectrophotometric, 23 electrochemical 24,25 and by chromatographic methods. [26][27][28] Similarly, CIN was determined spectrophotometrically, 29,30 electrochemically 31,32 and by different chromatographic methods [33][34][35][36][37][38][39] either alone or in combination with other drugs and related impurities. On the other hand, DMH and CIN were simultaneously assayed by spectrophotometric, 40,41 TLC-densitometric 42,43 and HPLC 43,44 methods.…”
Section: Introductionmentioning
confidence: 99%